2011
DOI: 10.1007/s11075-011-9447-8
|View full text |Cite
|
Sign up to set email alerts
|

Error analysis of Jacobi derivative estimators for noisy signals

Abstract: International audienceRecent algebraic parametric estimation techniques (see \cite{garnier,mfhsr}) led to point-wise derivative estimates by using only the iterated integral of a noisy observation signal (see \cite{num0,num}). In this paper, we extend such differentiation methods by providing a larger choice of parameters in these integrals: they can be reals. For this, %as in \cite{num0,num}, the extension is done via a truncated Jacobi orthogonal series expansion. Then, the noise error contribution of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 34 publications
0
84
0
Order By: Relevance
“…The objective is to estimate the n th order derivative of x using x ̟ . For this purpose, we apply a class of algebraic differentiators involving Jacobi polynomials, which were introduced in [7,8] using a recent algebraic parametric method (see [13] for other algebraic differentiators).…”
Section: Synthesis On Jacobi Differentiatormentioning
confidence: 99%
See 4 more Smart Citations
“…The objective is to estimate the n th order derivative of x using x ̟ . For this purpose, we apply a class of algebraic differentiators involving Jacobi polynomials, which were introduced in [7,8] using a recent algebraic parametric method (see [13] for other algebraic differentiators).…”
Section: Synthesis On Jacobi Differentiatormentioning
confidence: 99%
“…An error bound based on the integral formula given in (5) was proposed in [13] (p. 90) for this kind of noise errors. Moreover, it was shown that the Jacobi differentiator D (n) κ,µ,T,q x ̟ (t 0 − T ξ) can eliminate a (n − 1) th order structured perturbation.…”
Section: Error Analysis In Continuous Casementioning
confidence: 99%
See 3 more Smart Citations